Impact of contact resistance on the electrical properties of MoS2 transistors at practical operating temperatures - Giannazzo, Filippo; Fisichella, Gabriele; Piazza, Aurora; Di Franco, Salvatore; Greco, Giuseppe; Agnello, Simonpietro; Roccaforte, Fabrizio (Beilstein Journal of Nanotechnology, 2017)
Molybdenum disulphide (MoS2) is currently regarded as a promising material for the next generation of electronic and optoelectronic devices. However, several issues need to be addressed to fully exploit its potential for field effect transistor (FET) applications. In this context, the contact resistance, RC, associated with the Schottky barrier between source/drain metals and MoS2 currently represents one of the main limiting factors for suitable device performance. Furthermore, to gain a deeper understanding of MoS2 FETs under practical operating conditions, it is necessary to investigate the temperature dependence of the main electrical parameters, such as the field effect mobility (μ) and the threshold voltage (Vth). This paper reports a detailed electrical characterization of back-gated multilayer MoS2 transistors with Ni source/drain contacts at temperatures from T = 298 to 373 K, i.e., the expected range for transistor operation in circuits/systems, considering heating effects due to inefficient power dissipation. From the analysis of the transfer characteristics (ID−VG) in the subthreshold regime, the Schottky barrier height (ΦB ≈ 0.18 eV) associated with the Ni/MoS2 contact was evaluated. The resulting contact resistance in the on-state (electron accumulation in the channel) was also determined and it was found to increase with T as RC proportional to T3.1. The contribution of RC to the extraction of μ and Vth was evaluated, showing a more than 10% underestimation of μ when the effect of RC is neglected, whereas the effect on Vth is less significant. The temperature dependence of μ and Vth was also investigated. A decrease of μ proportional to 1/Tα with α = 1.4 ± 0.3 was found, indicating scattering by optical phonons as the main limiting mechanism for mobility above room temperature. The value of Vth showed a large negative shift (about 6 V) increasing the temperature from 298 to 373 K, which was explained in terms of electron trapping at MoS2/SiO2 interface states.
Keywords: contact resistance; mobility; MoS2; temperature dependence; threshold voltage